The bamboo mat board, a new technological proposal - Mora Rodríguez, Lena; Hernández González, Jorge F.; Martirena Hernández, José F.; Ariel Jiménez, Sandy (Revista Ingeniería de Construcción, 2008)
This paper presents a study that proposes the use of bamboo as a new laminated wood technology. The technology uses pressed fabrics of bamboo placed in orthogonal directions to build mat boards that can replace wood in certain structural elements. Bamboo mat boards, made with Bambusa Vulgaris Schrab using different temperatures and pressure during fabrication, are characterized in the lab by means of mechanical testing